Comparing Arthur Miller, Tennessee Williams and Edward Albee - Turku, Marsela; Gokaj, Rregjina (Mediterranean Journal of Social Sciences, 2012)
Arthur Miller and Tennessee Williams, who emerged as playwrights in the post-war world, after the 1945, brought AmericanDrama to prominence and dominated the American theatre for nearly a decade and a half. Both began their careers as politicalplaywrights by responding to the economic and social realities of the age. After the 1950 another major figure appeared and provokedradical experimentation by combining aesthetic innovation with political revolt. His name was Edward Albee. All these figures played anenormous role in the process of transformation and innovation in the American theatre. The three of them with their talents, theiraesthetic experimentation and political beliefs made the American theatre a ‘fascinating phenomenon.’ Although they are a product ofthe same nation, including political and cultural background, they are still very different in the way they present to the public the socialdrama, the transformation of the American dream, the character they choose to present their anxieties and the background theyemphasize; thus their means of connecting fact and fiction, language and image, reality and drama are different. Therefore, this paperaims to present an overview of the differences and similarities of their styles, language, the nature of their characters, their theatricalperformance, the innovation that each of them brought into the American theatre.